Long Term patency of Tunneled catheters in End Stage Renal Disease patients for vascular access- A single center study - Azhar Ali Khan, Ahmed Ayyaz, Maryam Javed, Waqar Ahmed, Farooq Ahmed, Azhar Waheed Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To look for the success and survival rate of tunneled catheters in hemodialysis patients. Design: Prospective study Duration & place of study: Department of Nephrology, Shaikh Zayed Hospital, Lahore from January 2017 to January 2018. Methodology: This study comprised of 71 consecutive subjects in whom tunneled catheters were inserted. The ESRD patients requiring permanent access for hemodialysis because of AVF failure, cardiomyopathy, waiting time for AVF maturation or renal transplantation were selected, those with previous permanent catheter insertions were excluded. The catheter was inserted in right internal jugular vein with doppler ultrasound. Result: The study included 71 patients; average age was 41±13 years, of them 43 were males. The success rate to insert catheter in an ideal location was observed in 73.2% and in non-ideal place in 26.8%patients. It was removed in67.6% and remained in situ till end of study in 32.4% patients. Functional AV fistula, renal transplantation and resolving AKI were elective reasons to remove catheters in 40%, 29% and 2% patients. The mean time of duration where tunneled catheter continued to serve as a vascular access and removed electively without catheter related problems was significantly different with Conclusion: The success rate of permanent catheter insertion was 99.2 % in our study. The catheter insertion under doppler ultrasound vision by a nephrologist offers a long lasting, safe and reliable alternative to restore a vascular access.